Consequences of Recent Southern Hemisphere Winter Variability on Polar Mesospheric Clouds - Siskind, David E; Stevens, Michael H; Hervig, Mark; Sassi, Fabrizio; Hoppel, Karl; Englert, Christoph R; Kochenash, Andrew J (2011)
Variations in the Southern Hemisphere (SH) winter of 2007, 2008 and 2009 had important consequences on polar mesospheric clouds (PMCs) observed in the corresponding Northern summers. Specifically, the stratospheric SH winter of 2007 was observed to be warmer than in 2008 and 2009. Using the high altitude analysis from the Navy Operational Global Atmospheric Prediction System- Advanced Level Physics High Altitude (NOGAPS-ALPHA) forecast/assimilation system we show that this warmth was linked to similar temperature increases in the high latitude summer mesosphere. These temperature changes led to a dramatic reduction in PMC occurrence (factor of 5 6) recorded by the SHIMMER instrument at sub-arctic latitudes and a factor of 2 decrease in total ice water content in PMCs seen by the SOFIE instrument on the NASA AIM satellite. Microphysical modeling confirms the overall effect of these temperature changes on PMCs at high latitudes; however, a detailed comparison of the cloud occurrence with the SHIMMER data for all three years shows that the clouds are associated with a surprisingly wide range (130 165 K) of temperatures Published in Journal of Atmospheric and Solar-Terrestrial Physics, v73 p2013 2021, 2011.